A theoretical model for functionally graded shape memory alloy cylinders subjected to internal pressure. Issue 7 (13th December 2016) - Liu, Bingfei; Hu, Shilong; Zhang, Wei; Zhou, Rui; Zhang, Yanan; Zhu, Yuping
Abstract: Abstract : A theoretical model for the Functionally Graded Shape Memory Alloy (FG-SMA) cylinders subjected to internal pressure is investigated. The gradient properties in this work are embodied in the Young's modulus and Poisson's ratio gradient through the thickness of the cylinder. The critical transformation stresses and maximum formation strain are all assumed to be constant. Combining the elasticity and exponential function of the Young's modulus and Poisson's ratio with the different gradient parameters, the elastic stress distributions and displacement distributions for the FG-SMA cylinder under the internal pressure are obtained, respectively. To get the theoretical solution, the Tresca yield function and the ideal elastic–plastic constitutive model are selected for the shape memory alloy to illustrate the phase transformation. The relationships between the internal pressure and total strain at the internal radius with different gradient parameters are then given, and the results show that the total strains are greatly influenced by the different parameters.